Application of the iBox prognostication system as a surrogate endpoint in the TRANSFORM randomised controlled trial: proof-of-concept study - Aubert, Olivier; Divard, Gillian; Pascual, Julio; Oppenheimer, Federico; Sommerer, Claudia; Citterio, Franco; Tedesco, Helio; Chadban, Steve; Henry, Mitchell; Vincenti, Flavio; Srinivas, Titte; Watarai, Yoshihiko; et al. (BMJ open, 2021)
Objectives Development of pharmaceutical agents in transplantation is currently limited by long waits for hard endpoints. We applied a validated integrative risk-prognostication system integrative Box (iBox) as a surrogate endpoint to the TRANSFORM Study, a large randomised controlled trial, to project individual patient long-term kidney allograft survival from 1 year to 11 years after randomisation. - Design Post-hoc analysis of a randomised open-label controlled trial. - Setting Multicentre study including 186 centres in 42 countries worldwide. - Participants 2037 de novo kidney transplant recipients. - Intervention Participants were randomised (1:1) to receive everolimus with reduced-exposure calcineurin inhibitor (EVR+rCNI) or mycophenolic acid with standard-exposure CNI (MPA+sCNI). - Primary outcome measure The iBox scores were computed for each participant at 1 year after randomisation using functional, immunological and histological parameters. Individual long-term death-censored allograft survival over 4, 6 and 11 years after randomisation was projected with the iBox risk-prognostication system. - Results Overall, 940 patients receiving EVR+rCNI and 932 receiving MPA+sCNI completed the 1-year visit. iBox scores generated at 1 year yielded graft survival prediction rates of 90.9% vs 92.1%, 87.9% vs 89.5%, and 80.0% vs 82.4% in the EVR+rCNI versus MPA+sCNI arms at 4, 6, and 11 years post-randomisation, respectively (all differences below the 10% non-inferiority margin defined by study protocol). Inclusion of immunological and histological Banff diagnoses parameters in iBox scores resulted in comparable and non-inferior predicted graft survival for both treatments. - Conclusions This proof-of-concept study provides the first application of a validated prognostication system as a surrogate endpoint in the field of transplantation. The iBox system, by projecting kidney allograft survival up to 11 years post-randomisation, confirms the non-inferiority of EVR+rCNI versus MPA+sCNI regimen. Given the current process engaged for surrogate endpoints qualification, this study illustrates the potential to fast track development of pharmaceutical agents. - Trial registration number TRANSFORM trial: NCT01950819.iBox prognostication system: NCT03474003.
Gesehen am 26.01.2022